Building an ethical digital humanities community: Librarian, faculty, and student collaboration. Issue 2 (2nd October 2017) - Risam, Roopika; Snow, Justin; Edwards, Susan
ABSTRACT: This article examines work building a digital humanities community at Salem State University's Berry Library. The initiatives are comprised of a three-pronged approach: laying groundwork to build a DH center, building the DH project Digital Salem as a place-based locus for digital scholarship, and launching an undergraduate internship program to explore ethical ways of creating innovative research experiences for undergraduate students. Together, these initiatives constitute an important move toward putting libraries at the center of creating DH opportunities for underserved student populations and a model for building DH at regional comprehensive universities.